Population structure of the corals Orbicella faveolata and Acropora palmata in the Mesoamerican Barrier Reef System with comparisons over Caribbean basin-wide spatial scale (2016)
Studies of genetic diversity and population genetic structure in marine organisms are relevant to understanding populations’ variability, and therefore their ability to withstand environmental perturbations, their potential for resistance to local extinction and their natural rate of recovery. Population structure and genetic diversity were assessed at a regional spatial scale (i.e., Mesoamerican Barrier Reef System, MBRS) in two major reef building coral species Orbicella (formerly Montastraea) faveolata and Acropora palmata, and at a larger spatial scale (i.e., Caribbean-wide; MBRS, Panama, Venezuela and Puerto Rico) for A. palmata only. The most significant findings were as follows: (1) high genetic diversity and low clonality were found for both species, which is expected for O. faveolata but not for A. palmata, (2) both species showed low-to-moderate, yet significant population structure among populations along the MBRS; in particular, O. faveolata and A. palmata from Ambergris (Belize) and O. faveolata from Calabash (Belize) and A. palmata from Puerto Morelos (Mexico) showed some genetic differentiation from the rest of the MBRS populations, and (3) A. palmata from MBRS, Panama, Puerto Rico and Venezuela were grouped into four subregions that could be considered as management units. A more spatially detailed sampling program and the inclusion of recruits will be necessary to get a comprehensive understanding of coral population structure and current gene flow patterns in these two species. © 2014, Springer-Verlag Berlin Heidelberg.